1998
DOI: 10.3109/00048679809073872
|View full text |Cite
|
Sign up to set email alerts
|

Familial Bipolar Disorder: Preliminary Results from the Otago Familial Bipolar Genetic Study

Abstract: Psychiatric genetic research in New Zealand families is highly feasible. Emerging trends in the familial transmission of BPD include high rates of comorbidity, illness patterns based on polarity of index episode and frequent suicidal behaviour. Such trends will be delineated further as numbers accrue, perhaps enabling identification of more homogenous phenotypic subgroups than currently produced by diagnostic schemes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 22 publications
2
19
2
Order By: Relevance
“…Familial BD has been associated with elevated risk for PD (Edmonds et al, 1998; Johnson et al, 2000; MacKinnon et al, 2002; MacKinnon et al, 2003), SAD (DelBello and Geller, 2001), and phobias (Edmonds et al, 1998). PD is one of the most studied comorbid anxiety disorders in familial BD (MacKinnon et al, 2002; Wozniak et al, 2002; MacKinnon et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Familial BD has been associated with elevated risk for PD (Edmonds et al, 1998; Johnson et al, 2000; MacKinnon et al, 2002; MacKinnon et al, 2003), SAD (DelBello and Geller, 2001), and phobias (Edmonds et al, 1998). PD is one of the most studied comorbid anxiety disorders in familial BD (MacKinnon et al, 2002; Wozniak et al, 2002; MacKinnon et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Three populationbased studies conducted in Italy and USA, reported lifetime prevalence rates of comorbid OCD in BD patients ranging between 11.1% and 21% (3,23,24). In hospital-based studies, the lifetime prevalence of comorbid OCD in BD patients ranged between 1.8% and 35.1% (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) depending on the features of the BD study population included (schizoaffective disorder, bipolar type). When restricting the analysis to studies with sample size greater than 250, the OCD-BD prevalence range was narrower (3-13.6%) (24,26,27,31,38,39), and the mean prevalence rate of BD-I comorbidity was 15%, while BD-II was 12.6% (24,38,39).…”
Section: Included Studiesmentioning
confidence: 99%
“…The FIGS is a semi-structured interview designed specifically for use in family genetic studies for the purpose of gathering information. The FIGS has been used in a number of prior studies (e.g., Edmonds et al, 1998). In the present study the FIGS was administered to probands (asking about their biological mother and father), to mothers (asking about the proband and the proband’s father), and to fathers (asking about the proband and the proband’s mother).…”
Section: Methodsmentioning
confidence: 99%